Evaluation of the quality of postoperative care in neurosurgery at a national referral hospital - Doléagbénou, Agbéko Komlan; Djoubairou, Ben Ousmane; Lessiou, Mazimbè Florantine; Kpélao, Essossinam; Fatigba, Holden (Frontiers in Surgery, 2025)
BackgroundThe quality of postoperative care is a critical determinant of patient safety in neurosurgery, particularly in low-resource settings. This study evaluated the quality of postoperative care in the neurosurgery department of Sylvanus Olympio University Hospital in Lomé, Togo.MethodsWe conducted a descriptive, cross-sectional study from October to December 2024, including patients who underwent neurosurgical procedures and received postoperative care in the neurosurgery ward. Data were collected using a structured checklist, medical record audits, and patient satisfaction surveys.ResultsA total of 51 patients were included (mean age: 37.1 ± 21.6 years; male-to-female ratio: 4.67). Traumatic brain injury accounted for 45% of surgical indications. Compliance with perioperative procedural standards was observed in 64.9% of cases, while only 13.7% of postoperative prescriptions adhered to standard protocols. Postoperative complications occurring during the inpatient hospital stay were observed in 13.7% of patients, and the mortality rate was 1.96%. Despite systemic shortcomings, 64.7% of patients reported overall satisfaction with their care.ConclusionSubstantial gaps remain in the application of standardized postoperative procedures, particularly in documentation and timing of care. Strengthening written protocols, enhancing staff training, and institutionalizing regular audits may improve neurosurgical outcomes in low-resource settings.